Effect of Mindfulness Therapy and Aromatherapy Massage on Pain Perception, Quality of Life and Sleep Quality in Older Women With Chronic Pain - Saied Malihialzackerini; Sima Alemi; Khadijeh Abolmaali Alhosseini; Mohammad Khabiri (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: Aging is one of the phenomena in the field of global health. It is very important to pay attention to older adults psychologically and physically. This study aims to evaluate the effect of mindfulness therapy combined with aromatherapy massage on the psychological functions of older women with chronic pain. Methods & Materials: This is a quasi-experimental study with a pre-test, post-test, follow-up design using a control group. The study population consists of all older women with chronic pain referred to hospitals, clinics, and rehabilitation centers in the west of Tehran, Iran in 2017. By using a convenience sampling method, 30 women were selected based on inclusion and exclusion criteria and randomly divided into two matched groups. The intervention group underwent mindfulness group therapy plus aromatherapy massage at ten 120-min sessions while the control group received no intervention. Their pain perception, sleep quality, and quality of life as psychological functions were evaluated at baseline, at the end of intervention and 45 days later. Collected data were analyzed using the analysis of covariance method in SPSS v. 19 software. Results: The mindfulness therapy/aromatherapy massage significantly reduced the pain perception and its components and improved quality of life and sleep quality in the intervention group compared to the control group (P<0.05), and these effects remained stable in the follow-up phase. Conclusion: mindfulness therapy combined with aromatherapy massage improves the quality of life and sleep and reduces chronic pain in older women. It can be used as an effective intervention for improving general health and quality of life in older patients with chronic pain.